2017
DOI: 10.4196/kjpp.2017.21.1.19
|View full text |Cite|
|
Sign up to set email alerts
|

Betulin suppressed interleukin-1β-induced gene expression, secretion and proteolytic activity of matrix metalloproteinase in cultured articular chondrocytes and production of matrix metalloproteinase in the knee joint of rat

Abstract: We investigated whether betulin affects the gene expression, secretion and proteolytic activity of matrix metalloproteinase-3 (MMP-3) in primary cultured rabbit articular chondrocytes, as well as in vivo production of MMP-3 in the rat knee joint to evaluate the potential chondroprotective effect of betulin. Rabbit articular chondrocytes were cultured and reverse transcription-polymerase chain reaction (RT-PCR) was used to measure interleukin-1β (IL-1β)-induced gene expression of MMP-3, MMP-1, MMP-13, a disinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…They have attracted researchers' interest as drugs for the treatment of OA, among which betulin is one. It has biological activity including anti- inflammation (Ci et al, 2017;Ra et al, 2017). Therefore, this experiment mainly verifies whether betulin has a protective effect on OA.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…They have attracted researchers' interest as drugs for the treatment of OA, among which betulin is one. It has biological activity including anti- inflammation (Ci et al, 2017;Ra et al, 2017). Therefore, this experiment mainly verifies whether betulin has a protective effect on OA.…”
Section: Discussionmentioning
confidence: 70%
“…For example, betulin attenuates renal injury in septicemic rats by inhibiting TLR4/NF-κB signal pathway (Zhao et al, 2016). In addition, it has been found that betulin inhibits IL-1β-induced matrix metalloproteinase gene expression and production (Ra et al, 2017), suggesting that betulin may delay the progression of OA, but the mechanism on how exactly it slows down the development of inflammation is unclear; this study specifically elaborated the specific mechanism of betulin in the progress of OA. It is worth noting that the role of the AKT/Nrf2/HO-1/NF-κB signal axis in the progression of OA has not been clarified yet.…”
Section: Introductionmentioning
confidence: 85%
“…The present study observed that Galium-Heel ® decreased the expression of GLI-2 therefore, it could potentially prevent the early stages of fibrosis by maintaining homeostasis of the ECM. The effects of Galium-Heel ® on ECM modulation might be due to certain components contained in the formulation including: i) Acidum nitricum , which participates as a nitric oxide (NO) donor through the nitrate/nitrite/NO pathway, and is involved in the collagen synthesis mechanism (3639); ii) argentum metallicum and aurum metallicum are donors of the trace elements silver and gold respectively, and exert an antioxidant effect (40); iii) aurum metallicum regulates MMP expression (41); iv) phosphorus contributes to the tissue inhibitor of metalloproteinases synthetic pathways (42); v) calcium fluoratum is involved in the synthesis of MMP-2 and −9 (43); vi) Caltha palustris promotes collagen synthesis (44); vii) Juniperus communis controls the synthesis of collagen type I and III (45); viii) Betula pendula reduces the expression of MMP-3 (46,47); and ix) Pyrogenium and Thuja occidentalis exert an immunomodulating effect through stimulation of T helper type I immune response and the synthesis of MMPs (4850). In addition, it should be considered that the various components contained in the formulation could have an additive or a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Betulin, a natural anti-inflammatory compound dereived from Betulae cortex , was reported to inhibit IL-1β-induced gene expression of MMP-1, 3, and 13. Betulin blocked in vivo MMP-3 production in rat knee joint [ 95 ]. Biochanin A, an isoflavone derived from red clover, showed pontential anticancer, antiallergic, and anti-inflammatory effects [ 96 ].…”
Section: Molecular Targets Of Natural Products and Their Therapeutmentioning
confidence: 99%